Effects of Mathematics Intervention Program on theNumeracy Skills of Grade Six Pupils - Elomina, Lilibeth (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the effects of the Mathematics Intervention Program on the numeracy skills of Grade Six pupils in selected public elementary schools in Binangonan District, Schools Division Office of Rizal, during the School Year 2025–2026. Specifically, it assessed the extent of the program’s effects on pupils’ numeracy skills in terms of basic arithmetic and number sense, measurement and spatial reasoning, and problem solving and critical thinking. The study also examined the relationship between the perceived effects of the intervention and pupils’ academic performance in Mathematics.A descriptive survey research design and documentary analysis were employed. The respondents consisted of 398 Grade Six pupils, representing 50% of the total population of 796 pupils, selected through simple random sampling. A researcher-made questionnaire checklist was utilized to measure pupils’ perceptions of the effects of the Mathematics Intervention Program. Documentary analysis of pupils’ first-quarter average grades in Mathematics was conducted to determine academic performance.Findings revealed that most pupils were male, first-born, from families with two to three children, and belonged to low-income households. Results showed that the Mathematics Intervention Program had a high effect on pupils’ numeracy skills across all domains. No significant differences were found in the perceived effects of the program when grouped according to sex, sibling position, number of children in the family, monthly family income, and parents’ educational attainment. However, parents’ occupation showed a significant difference. Pupils demonstrated an overall Satisfactory level of academic performance. A significant positive relationship was found between the perceived effects of the intervention program and pupils’ academic performance.The study concluded that the Mathematics Intervention Program significantly supports pupils’ numeracy development and is positively associated with academic achievement. Implementation of the proposed action plan and continuous program evaluation are recommended
Keywords: Mathematics Intervention Program, numeracy skills, Grade Six pupils, academic performance, descriptive survey research